2004
DOI: 10.1016/s0010-938x(03)00149-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of applied tensile stress on intergranular corrosion of AA2024-T3

Abstract: The effect of uniaxial tensile stress on intergranular corrosion (IGC) of AA2024-T3 was studied using the foil penetration technique. Standard ASTM G49 fixed-displacement jigs were modified to allow the use of sheet samples, which were then attached to an electrochemical cell as in the foil penetration setup. The time for IGC to penetrate samples of varying thickness was monitored. This method provides a new approach to bridge the gap between IGC and intergranular stress corrosion cracking (IGSCC). Samples wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…Stressed L-T foil penetration data are also presented for comparison. 12 As was the case for the unstressed samples, the results from the L-T foil penetration experiments overlie those from the L-T radiography experiments. Also shown in Fig.…”
Section: Methodsmentioning
confidence: 82%
“…Stressed L-T foil penetration data are also presented for comparison. 12 As was the case for the unstressed samples, the results from the L-T foil penetration experiments overlie those from the L-T radiography experiments. Also shown in Fig.…”
Section: Methodsmentioning
confidence: 82%
“…Like exfoliation corrosion, the fissures could grow as a result of self-stressing by voluminous corrosion product formed at the grain boundary region. It has recently been shown that very low stresses (as low as 10% of the yield stress) normal to the elongated microstructure in wrought aluminum alloys can increase localized corrosion penetration rates significantly [36]. For the sharp fissures in this study, the wedging stress from the corrosion product is apparently sufficient to drive cracking despite the constraining effect of the unexposed surrounding material.…”
Section: Sharp Igc Fissure Mechanismmentioning
confidence: 52%
“…First industrial tests show that this material may show some sensitivity to intergranular corrosion in specific conditions. Intergranular corrosion can depend on several parameters as precipitation [11], crystallographic orientations [12][13] or mechanical stress application [14]. In this document, corrosion tests are presented in order to underline some parameters effect (external stress, internal stress and microstructure).…”
Section: Materials Of the Studymentioning
confidence: 99%